Satisfying the online food crave - Farah, Maya F. (2022)
The food and beverage (F&B) sector has witnessed a significant rise in online food ordering and delivery companies. Through the consumer journey framework, this study aims to uncover the triggers pertaining to each stage in this journey. An exploratory qualitative research approach was adopted: semi-structured interviews were conducted with 33 customers and 17 experts in the food industry from the Lebanese, Saudi Arabian, and Emirati markets. A systematic understanding of the journey was devised alongside the triggers per stage to help both restaurants owners and online food aggregators to further develop their penetration and retention of customers using such platforms. The growing shift in emerging markets from ordering food over the phone to placing an order through OFAs has brought several implications on the customer purchase decision, as well as on the restaurants’ business perspectives. While this has had a dual growing impact both on the customer journey at large, and the way in which restaurants operate and market themselves, this field is yet under-researched particularly in emerging markets in the Middle East.